THE MAMMALIAN/MECHANISTIC TARGET OF RAPAMYCIN COMPLEX 2 (MTORC2) AND ITS ROLE IN NERVOUS SYSTEM - Jeremić, Marija; Trajkovic, Vladimir; Markovic, Ivanka (Medicinski podmladak, 2024)
The mammalian /mechanistic target of rapamycin (mTOR) is a ubiquitously expressed multimeric serine/threonine protein kinase, which plays an important role in the regulation of cellular growth, metabolism, and survival. mTOR forms two, evolutionarily conserved, signalling complexes: mTOR complex 1 and 2 (mTORC and mTORC2). The role of mTORC1 as a central regulator of growth and metabolism has been extensively studied. In contrast, the role of mTORC2 and the signals regulating its activity are less understood. Genetic studies have revealed the important role of mTORC2 in normal neuronal structure and function. Furthermore, an altered mTORC2 signalling was reported in several neurodegenerative and neurodevelopmental disorders, as well as in epilepsy. This manuscript provides an overview of the current understanding of mTORC2, including its components and known functions in the regulation of various cellular processes, and in different nervous system disorders. Key words: mTORC2, nervous system disorders